Activity of N-acetyl-L-cysteine against Biofilm of Staphylococcus Aureus and Pseudomonas Aeruginosa on Orthopedic Prosthetic Materials. Issue 1 (January 2013) - Drago, Lorenzo; De Vecchi, Elena; Mattina, Roberto; Romanò, Carlo L.
Purpose: Staphylococcus aureus and Pseudomonas aeruginosa are frequently isolated from biofilm-associated orthopedic implant infections. This study assessed the activity of N-acetyl-L-cysteine at inhibitory and subinhibitory concentrations against biofilm formed by S. aureus and P. aeruginosa on prosthetic materials. Methods: S. aureus and P. aeruginosa biofilm on smooth polyethylene and sand-blasted titanium discs was determined by means of a spectrophotometric assay before and at 3, 6, and 18 hours after addition of N-acetyl-L-cysteine. Results: N-acetyl-L-cysteine was able to disaggregate biofilm produced by S. aureus and P. aeruginosa on polyethylene and titanium discs after 3 h of incubation. A different rate in eradication of biofilm produced by P. aeruginosa was seen between polyethylene and titanium (50% vs. 20% respectively vs. biofilm formed before treatment). Results were confirmed by confocal laser scanning microscopy. Conclusions: The results suggest a possible role of N-acetyl-L-cysteine in the treatment of orthopedic prosthetic infections.